Compliance constants: are they of any real use?. (19th July 2013) - Baker, Jon
Abstract : Abstract : It is demonstrated once again that compliance constants (diagonal elements of the compliance matrix) or their inverses, relaxed force constants, cannot be reliably used as indicators of the strength of weak interatomic interactions, such as hydrogen bonds, as has frequently been proposed in the mainstream scientific literature. They are a measure, not just of the direct interaction between two atoms, but also of the contribution from all the indirect, or through‐bond, interactions as well. Any approach involving compliance constants that purports to measure the strength of a specific chemical bond must find a way of removing the through‐bond interactions. It would seem likely that such an approach must therefore involve off‐diagonal elements of the compliance matrix and not just the diagonal elements. This article is categorized under: Structure and Mechanism > Molecular Structures